Previous treatment decreases efficacy of pralsetinib in RET fusion-positive non-small-cell lung cancer - Lei Wang; Yafei You; Wenzhuo He; Yu Hou; Lan Li; Li Wang; Chang Jiang; Jiahong Yi; Yaoxiong Xia; Liangping Xia (Frontiers in Medicine)
BackgroundPralsetinib is a selective RET inhibitor. The ARROW trial revealed that RET fusion-positive non-small-cell lung cancer (NSCLC) can benefit from pralsetinib with tolerable adverse events (AEs). However, the efficacy and safety of pralsetinib in real world has rarely been reported.Materials and methodsThis study reviewed the efficacy and safety of pralsetinib in RET fusion-positive NSCLC patients between March 2021 and December 2021. Progression-free survival (PFS) and overall survival (OS) were evaluated by a Kaplan-Meier analysis and log-rank test. A Cox regression model was performed to identify independent prognostic factors.ResultsA total of 28 patients were enrolled, and the median follow-up time was 18.1 months. The objective response rate and disease control rate of the whole cohort were 57.2% and 71.4%, respectively, and the median PFS and OS were 8.1 months [95% confidence interval (CI), 3.1–13.2] and 13.8 months (95% CI, 2.8–24.8), respectively. Baseline characteristics of the treatment naive group and pre-treated group were listed. The median PFS tended to be better in treatment naive group (18.3 vs. 8.0 months, P = 0.067), while the median OS were similar between the two groups (28.4 vs. 11.6 months, P = 0.308). Patients with Eastern Cooperative Oncology Group Performance Status (ECOG PS) score of 2 had worse median PFS comparing with those with ECOG PS score of 0–1 (3.8 vs. 12.6 months, P = 0.004). Besides, patients previously treated with platinum-based chemotherapy (PBC) also revealed worse median PFS comparing with those without previous PBC (8.0 vs. 18.6 months, P = 0.023). Furthermore, patients previously treated with anti-programmed death-1 (PD-1) antibody or multikinase inhibitors (MKIs) showed worse median OS compared with those without previous anti-PD-1 antibody (5.0 vs. 22.0 months, P = 0.002) or MKIs (6.2 vs. 28.4 months, P = 0.015). The most common AEs was increased aspartate aminotransferase (39.3%).ConclusionPralsetinib was effective in RET fusion-positive NSCLC with tolerable AEs in real-world practice. Efficacy of pralsetinib was decreased in patients previously treated with PBC, immunotherapy, or MKIs.